Effectiveness of Business Management Performance Badan Usaha Milik “Moinfeu” Desa Oelbiteno, Kecamtan Fatuleu Tengah, Kabupaten Kupang - Laurensius Rasak; Charles Kapioru; Paulus Un (Undana Press, 2022)
This research was conducted at Badan Usaha Milik Desa Moinfeu, Oelbiteno village, middle Fatuleu Sub district, Kupang Regency. The purpose os this study was to know about the application of manajemen principles and how much that gained by Badan Usaha Milik Desa Moinfeu business units, Oelbiteno Village middle Fatuleu Sub district, Kupang Regency. This study used a qualitative descriptive analysis, that interpreting the object as what it is. The results of this study snowed that Badan Usaha Milik Desa Moinfeu business units, Oelbiteno Village middle Fatuleu Sub district, Kupang Regency had not maximally yet on applied the managemant principles, which is the planning principle, and there was no employment contract that hind to members and there was no clear recruitment criterias for the employees. Due to the organitation’s principles, there was overlapping of work and about the leader’s principles, there was no leader,s role on managing Badan Usaha Milik Desa Moinfeu and about the principle of supervisory management, there were no indicators in conducting supervision. The results showed that the amountof acceptance of the agency has clear employee recruitment criteria, about the principleof organizing the Badan Usaha Milik Desa Moinfeu, they received IDR 8,000,000 in 2019. This revenue is divided based on Peraturan Desa Oelbiteno No. 6 of 2017 about the establishment of Badan Usaha Milik Desa on paragraph 29. Based on this division, the amount of income of is Rp.2,000,000 (25%), that is for raising invesment for Badan Usaha Milik Desa Moinfeu.